PENGARUH MEKANISME GOOD CORPORATE GOVERNANCE DAN INDEPENDENSI AUDITOR TERHADAP MANAJEMEN LABA - Fachrony Fachrony; Herry Laksito (Diponegoro Journal of Accounting, 2015)
The purpose of this research is to examine the influence of good corporate governance mechanisms like institutional ownership, managerial ownership, independent directors and audit committee towards earnings management in manufacturing companies. As well as to test the influence of auditor’s independency towards earnings management in manufacturing companies. Leverage, audit quality, profitability and company’s size used as control variable. The population in this study consists of all listed firms in Indonesia Stock Exchange in year 2010-2014. Sampling method used is purposive sampling. Based on the sampling criteria established that the companies that have the managerial ownership, as well as independent directors during the years 2010 to 2014 obtained by 45 companies. By using the method of merging data during 5 years of observation were obtained by 45 x 5 or obtained as many as 225 periods of data observations. After going through the stage of data processing, there are 11 outliers that should be excluded from the sample, so that the proper amount of the final sample is observed that as many as 214 of data observations. Data were analyzed using multiple regression analysis. The empirical result of this study show that institutional ownership and managerial ownership have positively significant influenced on earnings management. Independent directors has negatively significant influenced on earnings management. Audit committee and auditor’s independency had no significant influenced on earnings management.